Hazard Identification, Risk Assessment and Risk Control (Hirarc) for Lifting Operation at Condominium Construction in Sabah. - Alveriuse, Callixtus; A. Kadir, Zuritah; A. Malambut, Nicholas (Progress in Engineering Application and Technology, 2023)
A construction is a high-risk industry that encompasses a wide range of construction, alteration, and/or repair activities. Construction workers are exposed to a variety of risks such as falling from rooftops, falling from scaffolding, unprotected machinery, being struck by heavy construction equipment, electrocutions, silica dust, and asbestos. One of the high-risk activities is operation of lugging tower crane. The aim of this study is to conduct hazard identification, risk assessment and risk control (HIRARC) for lifting operation at condominium construction in Sabah. The first objective was to investigate occupational hazard that contributes to the increased number of reported occupational accidents, injuries and diseases related to lifting operation of tower crane at Condominium Construction in Sabah. Workplace inspection was implemented by using Hazard identification checklist during the inspection. Based on the inspection, the work activities were identified, and hazard were also being identified. The second objective is to assess hazards and associated risks related to Lifting operation of tower crane at Condominium Construction in Sabah also able to be achieved by conducting risk assessment on the hazard identified using risk matrix. It was found that there were four hazards involving four activities categorized under high level of risk. Finally, the third objective was to recommend control measures, by using Hierarchy of Control on the hazards identified. The risk control proposed were presented to the safety team for further improvement.